Antimicrobial Functionalization of Prolamine-Silica Hybrid Coatings with Fumaric Acid for Food Packaging Materials and Their Biocompatibility - Franziska Trodtfeld; Tina Tölke; Cornelia Wiegand (MDPI AG, 2022)
The interest of the food packaging industry in biodegradable, recyclable, and functional materials has steadily increased in recent years. The use of hydrogels in the food sector holds great potential for use in packaging systems or as carriers for bioactive substances. The synthesis of an oxygen barrier coating of prolaminic silica material and antimicrobial functionalization with fumaric acid for packaging materials described here is an elegant way to meet these requirements. The developed material achieved a significant antimicrobial activity against Escherichia coli and Staphylococcus aureus, two common clinical pathogens. Another pre-requisite of such materials is a high biocompatibility, which can be assessed using human cell models, to help ensure consumer safety. The biocompatibility was determined by luminescence adenosine triphosphate and photometric lactate dehydrogenase assays. No cytotoxic effects on human keratinocytes in vitro were found for the test materials.